Flux variations of cosmic ray air showers detected by LHAASO-KM2A during a thunderstorm on June 10, 2021*Supported in China by National Key R&D program of China (2018YFA0404201, 2018YFA0404202, 2018YFA0404203, 2018YFA0404204), NSFC (U2031101, 11475141, 12147208) and in Thailand by RTA6280002 from Thailand Science Research and Innovation. (1st January 2023) - Aharonian, F.; An 安, Q. 琪; , Axikegu; Bai 白, L.X. 立新; Bai 白, Y.X. 云翔; Bao 包, Y.W. 逸炜; Bastieri, D.; Bi 毕, X.J. 效军; Bi 毕, Y.J. 玉江; Cai 蔡, J.T. 金庭; Cao 曹, Zhe 喆; Cao 曹, Zhen 臻; et al.
Abstract: The Large High Altitude Air Shower Observatory (LHAASO) has three sub-arrays, KM2A, WCDA, and WFCTA. The flux variations of cosmic ray air showers were studied by analyzing the KM2A data during a thunderstorm on June 10, 2021. The number of shower events that meet the trigger conditions increases significantly in atmospheric electric fields, with a maximum fractional increase of 20%. The variations in trigger rates (increases or decreases) were found to be strongly dependent on the primary zenith angle. The flux of secondary particles increased significantly, following a trend similar to that of shower events. To better understand the observed behavior, Monte Carlo simulations were performed with CORSIKA and G4KM2A (a code based on GEANT4). We found that the experimental data (in saturated negative fields) were in good agreement with the simulations, assuming the presence of a uniform electric field of -700 V/cm with a thickness of 1500 m in the atmosphere above the observation level. Due to the acceleration/deceleration by the atmospheric electric field, the number of secondary particles with energy above the detector threshold was modified, resulting in the changes in shower detection rate.